A COMPARATIVE STUDY BETWEEN MEN AND WOMEN LANGUAGE STYLE: A CASE STUDY IN THE TONIGHT SHOW STARRING JIMMY FALLON - Jon Piter Situmorang; Lasma Kristina Sigiro (Muse: Jurnal of Art, 2024)
This is about language which is used by people has so many differences. The differences itself are associated with men and women which belong to gender. There are differences in spoken language. In this study, the writer is interested in investigating thecomparative of language style mostly use by men and women in The Tonight Show Starring Jimmy Fallon. The research problem of the study is (what kinds of language styles that are mostly used by men and women in The Tonight Show Starring Jimmy Fallon. This study used qualitative approach. In analyzing the data, the writer used theories by Martin Joss (1976). There were ten consisting of five men and five women.Men and women have different words choice. Men language form is found harsher while women language form is weaker and more polite. It means that, men and women still have their own language style because of the different types and aspects. In the communication purposes, the analysis shows that both men and women users in The Tonight Show Starrring Jimmy Fallon mostly communicate to express feeling and opinion rather than the other communication purposes such as report fact, solving problem, and develop and maintain rapport, In short, the writer finds the language style and communication purposes between men and women in The Tonight Show Starring Jimmy Fallon.